<span>-3,3(2/3x +1) -3(1 1/3 - 1 1/6 x )
- 33/10*(2/3х+1)-3(1/3-1/6х)
- 3/10*(11(2/3х+1)+10(1/3-1/6х))
- 3/10*(22/3х+11+10/3-5/3х)
- 3/10*(17/3х+43/3)
- 3/10*1/3*(17х+43)
- 1/10*(17х+43)</span>
2 1/8:в=2 19/28:3 3/4
17/8:в= 75/28: 15/4 = 75/28* 4/15
17/8х=5/7
х=5/7:17/8=5/7*8/17
х=40/119
..................................
Ответ:
Пошаговое объяснение:
1.
(2/3)⁽⁸ˣ⁺¹⁾=1,5⁽²ˣ⁻³⁾
(2/3)⁽⁸ˣ⁺¹⁾=(3/2)⁽²ˣ⁻³⁾
(2/3)⁽⁸ˣ⁺¹⁾=(2/3)⁽³⁻²ˣ⁾ ⇒
8x+1=3-2x
10x=2 |÷10
x=0,2.
Ответ: х=0,2.
3.
log√₅(5*√5)*log₀,₃√0,3:lg(10*√0,1)
1. log√₅(5*√5)=2*log₅(5¹'⁵)=2*1,5*log₅5=3.
2. log₀,₃√0,3=(1/2)*log₀,₃0,3=1/2.
3. lg(10*√0,1)=lg√10=(1/2)*lg10=1/2.
4. 3*(1/2):(1/2)=3.
5.
log₃(x²+6)<log₃5x ОДЗ: х>0.
x²+6<5x
x²-5x+6<0
x²-5x+6=0 D=1
x₁=2 x₂=3 ⇒
Ответ: x∈(2;3).